Modified Minkowski Fractal Unit Cell for Reflectarrays with Low Sensitivity to Mutual Coupling Effects - Sandra Costanzo; Francesca Venneri; Giuseppe Di Massa (International Journal of Antennas and Propagation)
A single-layer miniaturized reflectarray element with low sensitivity to mutual coupling effects of surrounding elements is presented in this paper. The configuration is proposed to preserve the effectiveness of the infinite array approach in those applications requiring reflectarrays with very small interelement spacing. The inherent ability of the proposed geometry to be adopted in highly miniaturized cells is demonstrated through an extensive analysis of mutual coupling effects on reflectarray phase design curves. In order to prove the independence of the proposed cell to mutual coupling effect, the phase curve variations due to the presence of different surrounding elements with respect to the case of identical cells are evaluated using the well-known extended local periodicity method. Small and negligible mutual coupling errors are retrieved for the proposed miniaturized unit cell, thus demonstrating lower sensitivity to mutual coupling adverse effects.